Creating engines of growth - Rowarth, Jacqueline (New Zealand Science Review, 2010)
Changes in the New Zealand science system have been approved by the Minister of Research, Science and Technology. This paper discusses the main recommendations, including how implementation focused on excellence and leadership can allow the CRIs to become the desired engines of growth for the economy.